2021
DOI: 10.21037/atm-20-5372
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted bipolar disorder is causally associated with an increased risk of breast cancer: a two-sample Mendelian randomization analysis

Abstract: Background: Epidemiologic findings suggested that bipolar disorder (BD) may be associated with an increased risk of breast cancer. However, there are few studies that comprehensively evaluating their correlation and the causal effect remains unknown. With a two-sample Mendelian randomization (MR) approach, we were able to investigate the causal relationship between genetically predicted BD and breast cancer risk. Methods: Utilizing 14 BD-related single nucleotide polymorphisms (SNPs) as instrumental variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The causality of BD and BC risk is controversial [41,42]. In our MR research, BD failed to be linked to BC incidence, and our results differ from the published studies [43]. Although more IVs for exposure-related SNPs were used in this article, the IVs used for exposure-related in this article included Asian populations [43].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The causality of BD and BC risk is controversial [41,42]. In our MR research, BD failed to be linked to BC incidence, and our results differ from the published studies [43]. Although more IVs for exposure-related SNPs were used in this article, the IVs used for exposure-related in this article included Asian populations [43].…”
Section: Discussioncontrasting
confidence: 73%
“…Although more IVs for exposure-related SNPs were used in this article, the IVs used for exposure-related in this article included Asian populations [43]. In contrast, the outcome-related IVs were from the European populations, leading to errors in the results [43].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted in 2022 that a number of breast cancer patients exhibited symptoms similar to those of post-traumatic stress disorder, which were thought to be mediated by chronic inflammation, such as NF-κB, AKt, p53, and other inflammatory pathways ( 70 ). Another MR analysis indicated that bipolar disorder was causally linked to a higher breast cancer rate ( 71 ). On the one hand, the reason why our conclusion differed from previous ones might be that the sample size of GWAS data was not large enough to produce statistical differences, on the other hand, previous results might be affected by a variety of biases or confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with bipolar disorder and their unaffected siblings under 50 years of age had a higher chance of developing breast cancer than those in the control group. The correlation between bipolar disorder and the younger population’s susceptibility to bipolar disorder and higher cancer risk could indicate a genetic overlap in the pathophysiology of neurodevelopment ( McGinty et al, 2012 ; Peng et al, 2021 ; Chen et al, 2022 ). When comorbid intellectual disability and/or birth defects are present, those with autism spectrum disorders are more likely than those without autism spectrum disorders to have cancer in their early years.…”
Section: Introduction: Background and Premisementioning
confidence: 99%